REPRESENTATION OF VERISIMILITUDE IN ANALYSIS OF FLASH FICTION - Kusuma Wijaya; Rommel Utungga Pasopati; Fransisca Irnidianis Magdalena Suyaji; Kheista Sasi Kirana; Salsabila Adinda Oktavia; Riska Dewi Ramadhani (Seminar Nasional Hasil Riset dan Pengabdian, 2024)
This article exposes matters of representations in the contexts of analysis of flash fiction. Flash fiction has never been into the spotlight due to its brevity compared to other canon literature. However, the simplicity of it emphasizes its complexities and specifications. Through qualitative method and explorative approach, this paper underlines that flash fiction is never limited by its short number of words. In analysis, first, the meanings involved in flash fiction are never limited by the number of words, but widened through experience and taste beyond the rigidity of definitions. Second, even many leading writers such as Ernest Hemingway and Gabriel Garcia Marquez also use this type of work as a form of simplification of their other works. Third, flash fiction relies on characters and plots by highlighting the tension between the fixed and the flexible, intention-interpretation, and even tone-mood. Fourth, flash fiction finds its uniqueness in the plot twists and extreme points of reality. Fifth, flash fiction handles representations by various cliches. Sixth, flash fiction approaches reality through explorative meanings in verisimilitude. In conclusion, flash fiction involves its verisimilitude not through transparent reality, but full of imagination starting from metaphors, representations, to subtext. Keywords Flash Fiction; Representation; Verisimilitude